2019
DOI: 10.1128/jvi.02086-18
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Mouse Model of HIV-1 Latency with Enrichment of Latent Virus in PD-1 + and TIGIT + CD4 T Cells

Abstract: Combination anti-retroviral drug therapy (ART) potently suppresses HIV-1 replication but does not result in virus eradication or a cure. A major contributing factor is the long-term persistence of a reservoir of latently infected cells. To study this reservoir, we established a humanized mouse model of HIV-1 infection and ART suppression based on an oral ART regimen. Similar to humans, HIV-1 levels in the blood of ART-treated animals were frequently suppressed below the limits of detection. However, the limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 108 publications
1
22
0
Order By: Relevance
“…For example, upregulation of PD-1 and CTLA-4 expression is associated with higher plasma viral loads and lower CD4 + T-cell counts. Enhancements in CTLA-4, TIM-3, LAG-3, and TIGIT expression in HIV-infected CD4 + T-cells are also associated with the integration of HIV-DNA in these cells [46,50,51,53,101,102]. Additionally, the upregulation of CTLA-4 in CD4 + T-cells was reported to cause a high level of CCR5 expression on CD4 + T-cells, thereby supporting a vigorous HIV-1 infection [48], which suggests that CTLA-4 upregulation by HIV infection could increase CD4 + T-cell susceptibility to HIV infection.…”
Section: Hiv-specific T-cell Exhaustion Accompanies Immune Checkpointmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, upregulation of PD-1 and CTLA-4 expression is associated with higher plasma viral loads and lower CD4 + T-cell counts. Enhancements in CTLA-4, TIM-3, LAG-3, and TIGIT expression in HIV-infected CD4 + T-cells are also associated with the integration of HIV-DNA in these cells [46,50,51,53,101,102]. Additionally, the upregulation of CTLA-4 in CD4 + T-cells was reported to cause a high level of CCR5 expression on CD4 + T-cells, thereby supporting a vigorous HIV-1 infection [48], which suggests that CTLA-4 upregulation by HIV infection could increase CD4 + T-cell susceptibility to HIV infection.…”
Section: Hiv-specific T-cell Exhaustion Accompanies Immune Checkpointmentioning
confidence: 99%
“…Therapy targeting immune checkpoint proteins shows potential for eliminating HIV reservoirs. Multiple immune checkpoint receptors were found to be expressed on latent HIV-1 reservoir cells and associated with the amount of integrated HIV-DNA [102,124,125]. During ART, the CD4 + T-cells expressing PD-1, TIGIT, and LAG-3 alone or in combination were highly enriched for integrated viral genomes as compared with immune checkpoint receptor-negative CD4 + memory T-cells isolated from HIV-infected individuals [101].…”
Section: The Upregulation Of Immune Checkpoint Proteins Helps To Estamentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 9 We and others have shown that the BLT mouse model can be efficiently infected with HIV and forms authentic post-integration latency in resting CD4 + T cells. 9 , 10 , 11 , 12 , 13 Viral loads can be suppressed using clinically relevant ART, and if ART is stopped, then viral replication quickly rebounds, as occurs with infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Early initiation of antiretroviral treatment (ART) in HIV infected individuals does not return TIGIT/CD115 to normal levels on CD8 + T cells [37]. Additionally, the co-expression of TIGIT with immune checkpoint inhibitor PD-1 marks CD4 + T cells harboring latent virus [45][46][47]. These data suggest that the TIGIT/CD155/CD112 pathway in T cells could contribute to HIV pathogenesis.…”
Section: Introductionmentioning
confidence: 99%